PENGARUH KEKERASAN VERBAL ORANGTUA TERHADAP TINGKAT KEPERCAYAAN DIRI ANAK USIA DINI DI TK MISI BAGI BANGSA CIKARANG - Elika Meisari Zalukhu; Arie Widiyastuti, Rita Intan Anggraeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Elika Meisari Zalukhu. The Relationship between Parental Verbal Violence and the Level of Self-Confidence of Early Childhood Children at Mission Kindergarten for the Nation, Cikarang. Early Childhood Education Teacher Education Study Program. Faculty of Education. Panca Sakti University, Bekasi, 2025. This study analyzes the effect of parental verbal abuse and the self-confidence of early childhood children at Misi Bagi Bangsa Kindergarten, Cikarang. Researchers observed that some children at Misi Bagi Bangsa Kindergarten, Cikarang, still experience verbal abuse. This often leads to them being reluctant to speak up in front of their peers and even having difficulty expressing their opinions when teachers ask simple questions. This study aimed to determine whether parental verbal abuse positively impacts the self-confidence of early childhood children at Misi Bagi Bangsa Kindergarten, Cikarang. The researchers used a quantitative research method with simple multiple linear regression analysis. The results indicate that parental verbal abuse has a positive and significant impact on the self-confidence of early childhood children, with an influence value of 1.184 and a significance value of 0.00. The coefficient of determination (R-Square) was 0.809, indicating that overall, parental verbal abuse impacts operational efficiency by 80%.